Black bears - Daly, Timothy M. (Nature's children (New York, N.Y.), 2013)
"While several distinct bear species live throughout the world, the most common and well known is the black bear. Readers will find out what sets these powerful mammals apart from their relatives, from what they eat and where they live to how they interact socially and how they raise their young. They will also learn about the complicated relationship between black bears and humans"--Provided by publisher.